Efektivitas Pembelajaran Menggunakan Aplikasi Edmodo Terhadap Hasil Belajar Penyajian Data Di Kelas IV SD - Hastuti, Erni; Ariani, Yetti; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis article was written for relevant information to the use of materials to study presentation data in grade IV elementary. Research data is collected quantitatively with experimental research using pre experimental method. Based on data analysis, the results obtained by using t-test (t-test) obtained = 12.03 and 〖t〗 _ (table (0,05) 16)) = 2.12 at the real level α = 0.05 Tcount province> so H1 on this experience accept and H0 rejected. So got difference in learning results presentation of data between students who learn to use edmodo applications before put into data presentation of data with the results of learning presentation of data students who learn to use educational applications entered into the data of fourth grade students elementary school Al-Azhar Bukittinggi Lesson 2017/2018. Thus, the results of the research indicate that the applications contained therein already have useful material for the presentation data. Keywords: Learning Effectiveness, Edmodo Applications, Learning Outcomes